117k views
3 votes
What is (-4x²-3x+8) subtracted from (2x2² + 5x - 7)?​

2 Answers

6 votes

Answer:

6x² + 8x - 15

Explanation:

2x² + 5x - 7 - (- 4x² - 3x + 8) ← distribute parenthesis by - 1

= 2x² + 5x - 7 + 4x² + 3x - 8 ← collect like terms

= 6x² + 8x - 15

User Hovercouch
by
5.1k points
3 votes

Answer:


6x^2+8x-15

Explanation:

Given expression:


(2x^2+5x-7)-(-4x^2-3x+8)


\textsf{Apply\:the\:distributive\:law}\quad \:-\left(-a-b\right)=a+b:


\implies 2x^2+5x-7+4x^2+3x-8

Collect like terms:


\implies 2x^2+4x^2+5x+3x-7-8

Combine like terms:


\implies 6x^2+8x-15

User Ekrem Solmaz
by
5.4k points